La dudosa vida de Sexto Empírico (Argos, 2025)
In the present paper we attempt to clarify and to deepen the different problems and the current theories about the real existence of the author known as Sextus Empiricus. The results, although preliminary, will suggest us decisive biographical elements that we deem that will be not only of utility for future researches on the field but also of help for advanced readers and their interpretation exercise of the philosophy of this skeptic.